2014
DOI: 10.1074/jbc.m113.541110
|View full text |Cite
|
Sign up to set email alerts
|

Sterol Regulatory Element-binding Protein-1 (SREBP-1) Is Required to Regulate Glycogen Synthesis and Gluconeogenic Gene Expression in Mouse Liver

Abstract: Background:The role of SREBP-1 in regulating carbohydrate metabolism is unclear. Results: Silencing SREBP-1 reduced glycogen buildup and expression of genes involved in glycogen synthesis as well as gluconeogenesis. Conclusion: SREBP-1 is needed to regulate carbohydrate metabolism during the fed state. Thus, its depletion does not improve insulin resistance. Significance: This report provides a novel function for SREBP-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(77 citation statements)
references
References 45 publications
3
67
0
Order By: Relevance
“…In agreement with previous studies, we found that SREBP1 and DGAT2 are greatly modulated by Plin2. SREBP1 is the master regulator of genes involved in de novo lipogenesis, while DGAT2 is the enzyme of the last step in the pathway of TAG synthesis . Different studies showed that these two genes are involved in lipid accumulation and in the control of muscle mass.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with previous studies, we found that SREBP1 and DGAT2 are greatly modulated by Plin2. SREBP1 is the master regulator of genes involved in de novo lipogenesis, while DGAT2 is the enzyme of the last step in the pathway of TAG synthesis . Different studies showed that these two genes are involved in lipid accumulation and in the control of muscle mass.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, mice with liver-specific knockout of the gene encoding the protein phosphatase Shp1 develop NAFLD, but are protected from insulin resistance 100 . Hepatic carbohydrate responsive element-binding protein and sterol regulatory element-binding protein-1 have recently been independently implicated in dissociating NAFLD and insulin resistance in mice and humans 101,102 . In addition, mice with the gene encoding the lipase activator CGI-58 knocked down have profound hepatic steatosis due to suppression of hepatic triglyceride lipolysis.…”
Section: Dissociation Of Nafld and Hepatic Insulin Resistancementioning
confidence: 99%
“…However, recent models wherein Akt is unable to inhibit GSK3 have called into question the physiological relevance of GSK inhibition on glycogenesis [154156]. Our group and others have implicated mTORC1-dependent activation of SREBP1 as a novel regulator in liver glycogen synthesis [151,157]. Similarly, a mTORC1/SREBP1 pathway plays an important role in lipogenesis in concert with the effects of mTORC1 on the phosphatidic acid phosphatase Lipin [143,148,158160].…”
Section: Glycogen and Lipid Synthesismentioning
confidence: 99%